The Effect Of Isotonic Solution Immersion On Tooth Enamel Hardness After Topical Application Of CPP-ACPF And fTCP - Sri Wahyuni; Rini Bikarindrasari; Mutiara Nur Fauziah (Jurnal Kesehatan Gigi, 2022)
Introduction:  The  addition  of  topical  CPP-ACPF  and  fTCP  on  tooth  enamel  can improve enamel hardness due to remineralization process. Demineralization can occur during  acid  environment  in  the oral  cavity  and  enamel  hardness  can  decrease. Objective:  To determine  the effect of isotonic solution immersion  and compare tooth enamel hardness after CPP-ACPF and fTCP application. Methods: Thirty six crowns of  maxillary first premolars were divided into three groups, each consisted of 12 tooth crowns.  The  baseline  hardness  of  each  sample  (pre-test)  was  tested  using  Vicker’s Hardness Tester Digital. Afterwards,  CPP-ACPF  was applied to group A, fTCP was applied to group B, and artificial saliva to group C (control) for 24 hours, then the hardness was re-assessed  (post-test 1). Immersion in isotonic solution was conducted for  24  hours  to  simulate  demineralization  process,  then  enamel hardness  was  re- assessed  (post-test  2). Results:  Paired  t-test  on post-test  1 revealed  that all groups showed  significant  increase  and  post-test  2  showed  significant  enamel   hardness decrease.  The results  of  one-way  ANOVA  on  pre-test  showed  that  there  was  no significant difference, while post test 1 and post-test 2 revealed significant difference. Post-Hoc Bonferroni test showed that there was no statistically significant difference of enamel hardness between groups. Conclusion: There was an effect of isotonic solution immersion on tooth enamel hardness that were given topical CPP-ACPF and fTCP.